A Multi-Disciplinary, Holistic Approach to Networked Learning Research: A Critique of a Large-scale Empirical Study into Student Online Learning Experiences - Timmis, Sue; O'Leary, Ros; Weedon, Elisabet; Martin, Kerry (Proceedings of the International Conference on Networked Learning, 2004)
In this paper, we present our collective reflections on the methodological and collaborative experiences embedded within a cross-disciplinary study of student online learning experiences. The paper will present the theoretical underpinnings for the research design, describe the chosen framework and methods, and identify methodological issues and lessons arising from the implementation of this research. In addition, we will show how the workings of the multi-disciplinary, distributed research team and collaborative methods contributed to the project and to building research capacity in subject communities.